1997
DOI: 10.1073/pnas.94.12.6126
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen promotes DNA synthesis past template lesions by mammalian DNA polymerase δ

Abstract: Consistent with previous observations, proliferating cell nuclear antigen (PCNA) promotes DNA synthesis by calf thymus DNA polymerase ␦ (pol ␦) past several chemically defined template lesions including model abasic sites, 8-oxo-deoxyguanosine (dG) and aminof luorene-dG (but not acetylaminof luorene-dG). This synthesis is potentially mutagenic. The model abasic site was studied most extensively. When all deoxyribonucleoside triphosphates and a template bearing a model abasic site were present, DNA synthesis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 66 publications
(35 reference statements)
9
90
1
Order By: Relevance
“…We therefore examined whether purified human PCNA, a sliding clamp known to stimulate the processivity of the replicative DNA polymerases pol␦ and pol⑀ (18 -20), increases the extent of DNA synthesis by GST/pol. The ability of PCNA to stimulate the activity of pol␦ on short oligonucleotide-derived primer-templates has been observed previously (21). As shown in Fig.…”
Section: Human Dinb1mentioning
confidence: 49%
“…We therefore examined whether purified human PCNA, a sliding clamp known to stimulate the processivity of the replicative DNA polymerases pol␦ and pol⑀ (18 -20), increases the extent of DNA synthesis by GST/pol. The ability of PCNA to stimulate the activity of pol␦ on short oligonucleotide-derived primer-templates has been observed previously (21). As shown in Fig.…”
Section: Human Dinb1mentioning
confidence: 49%
“…In vitro bypass studies with purified mammalian DNA polymerases have shown that most polymerases can bypass abasic sites, at least under certain conditions (11,24,(50)(51)(52)(53)(54)(55). This underscores the need for in vivo TLR data to determine the physiological role of specific DNA polymerases in bypass of a particular lesion.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is a processivity factor of DNA polymerase d (pol d), an enzyme involved in both DNA replication and NER (Kelman, 1997). Excess PCNA has been shown to promote DNA synthesis past template lesions (Mozzherin et al, 1996(Mozzherin et al, , 1997. Therefore, increased PCNA expression induced by Tax appears to suppress NER and allow replication of damaged DNA, providing a basis for the introduction of mutations into HTLV-I infected cells.…”
Section: Effect Of Tax On Cellular Dna Repairmentioning
confidence: 99%